Grimm. Season three [videorecording (DVD)] - Hornsby, Russell; Mitchell, Silas Weir; Giuntoli, David, 1980- (Grimm (Television program), 2014)
Nick is stronger than ever with his partner Hank and reunited love Juliette by his side as he tracks down Wesen criminals with renewed determination. But things are changing as the ties between humans and the Wesen world will become even more irrevocably intertwined.